The Deep Integration of Artificial Intelligence and the Automotive Industry: Technological Applications, Industrial Transformation and Future Trends - Jiabin Liao (Asia Pacific Economic and Management Review, 2026)
Against the backdrop of deep integration between the digital economy and the real economy, artificial intelligence is comprehensively reshaping the automotive industry’s technological framework, production models, and value structures. Centred on the core logic of AI empowering the entire automotive industry chain, this paper systematically examines its application pathways and enabling outcomes across R&D design, manufacturing, supply chain management, and marketing services. It distils three core transformative characteristics: iterative shifts in industrial competition focal points, reconfiguration of ecosystem structures, and dual upgrading of value and standards. Building upon this foundation, the paper anticipates future trends characterised by multidimensional deepening of technological convergence, comprehensive strengthening of industrial synergy, and bidirectional empowerment through scenario applications and security systems. Concurrently, it precisely identifies key challenges including technological bottlenecks, barriers to industrial collaboration, lagging institutional adaptation, and user perception biases. Addressing these challenges, the paper proposes targeted development recommendations across four dimensions: technological innovation breakthroughs, optimisation of industrial chain collaboration, refinement of institutional frameworks, and cultivation of user markets. Research indicates that artificial intelligence not only enhances efficiency and optimises quality across automotive industry segments but also propels the sector’s transformation from mechanical manufacturing to intelligent manufacturing, and from single-product focus to full lifecycle services. Deepening this integration represents a strategic opportunity for China to evolve from a major automotive nation into a leading automotive power, offering a Chinese solution for the global automotive industry’s intelligent transformation.